Salabat made instant - Kintanilla, Kenneth G. (College of Engineering, 1997)
Product: Instant salabat in powdered form -- Plant site: Nasugbu, Batangas -- Annual capacity: 85,800 kg from 1999 to 2003, 170339 kg from 2004 to 2008 -- Price: P14.80 per 60 grams, P28.00 per 260 grams, P22.80 per 100 grams -- Annual production cost: P 7,782,159.88 for first five years, P 10,606,132.53 for next five years -- Average annual net profit: P 5,169,344.03 -- Annual return on investment: 64.6% -- Payback period: 1.32 years